Economic sanctions in international law - Jana Ilieva; Aleksandar Dashtevski; Filip Kokotovic (UTMS Journal of Economics, 2018)
Economic sanctions are a very important topic in the present international relations but also very common headlines in the daily news. At the present time, they become an increasingly prevalent measure for disciplining states' unacceptable behaviour by a ban on trade and disruption of financial relations for political purposes. Economic sanctions can be imposed by an international organization, being there multilateral (UN) or regional (such as EU) but also can appear in form of unilateral (autonomous) act of a state. The latter is broadly criticized as being contrary to international law hence these unilateral sanctions face lack of support by the international lawyers. On the other hand, there exists no universally accepted mechanism (authoritative international body) in international law to determine if one economic sanction is lawful or not thus this issue remains one of the least developed area therein. Economic sanctions 'effectiveness is another opened question that requires prompt reaction. Therefore, the existing relationship between economic sanction and international law is controversial and opens perspectives for different approaches and tensions in the international arena.
Keywords: K33; F51; 330; economic sanctions; states; international law; UN; EU; Russia